2016
DOI: 10.1371/journal.pone.0164082
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in the Rhizospheres of Three Mangrove Tree Species from Beilun Estuary, China

Abstract: The bacterial communities played important roles in the high productivity mangrove ecosystem. In this study, we investigated the vertical distributions of rhizosphere bacteria from three mangrove species (Bruguiera gymnorrhiza, Kandelia candel and Aegiceras corniculatum) in Beilun Estuary, China using high throughput DNA pyrosequencing of the 16S rRNA gene. Phylogenetic analysis showed that bacterial communities from mangrove rhizosphere sediments were dominated by Proteobacteria (mostly Deltaproteobacteria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 41 publications
10
50
0
3
Order By: Relevance
“…Mangrove forests are complex and dynamic ecosystems that are highly variable in several physicochemical conditions including salinity, flooding, light, temperature, and nutrient, which promote the bacterial diversity. It was reported that mangrove species were the main factors influencing their rhizosphere bacterial communities [26]. The run-off water in tourist sites may come from various sources such as swimmers, trash disposal from tourists, domestic wastewater, and illegal discharge from recreation boats [24].…”
Section: Discussionmentioning
confidence: 99%
“…Mangrove forests are complex and dynamic ecosystems that are highly variable in several physicochemical conditions including salinity, flooding, light, temperature, and nutrient, which promote the bacterial diversity. It was reported that mangrove species were the main factors influencing their rhizosphere bacterial communities [26]. The run-off water in tourist sites may come from various sources such as swimmers, trash disposal from tourists, domestic wastewater, and illegal discharge from recreation boats [24].…”
Section: Discussionmentioning
confidence: 99%
“…As bacteria of the phylum Chloroflexi were more significantly detected in the CF-biofilm than in AS, it implies that the phylum Chloroflexi contributed to reducing N 2 O emission to adhere within the CF carrier. In addition, the order envOPS12, which belongs to the phylum Chloroflexi, has been found in a wide range of anaerobic environments, such as freshwater, sediments, marine water, sponges, anaerobic sludge bioreactors and anammox reactors [27,28]. Because envOPS12 grows in anaerobic conditions, it was hypothesized that a large quantity of envOPS12 was detected because the CF-biofilm (DL) was in an anaerobic condition.…”
Section: Discussionmentioning
confidence: 99%
“…2B, 3B and Additional le 2: Table S2). To avoid the effects of rhizosphere in mangroves [25], we only collected the bulk sediments away from the plant roots. However, the location and depth were still the signi cant spatial dimensions that shaped the microbial communities in mangrove sediments, suggesting that the distribution of microbial communities in mangrove sediments was highly territorialized in a fairly close sampling range (e.g., in the same city for sampling).…”
Section: Discussionmentioning
confidence: 99%